Mathematics Addendum - class 4 - Iranga Galhenage,Don Shenal; Ms.Nosheen Hsaan; Ms.Siddiqua Maqsood (Ideal Furnishers, 2022)
This addendum supplements the Class 4 mathematics curriculum, focusing on key concepts and providing additional resources and activities to enhance student understanding. It covers essential topics such as number sense, operations (addition, subtraction, multiplication, division), fractions, decimals, measurement, geometry, and basic data interpretation. Recommended activities include hands-on projects, math games, and real-life applications to engage students and reinforce their learning. The goal is to foster a deeper appreciation for mathematics and encourage curiosity and problem-solving skills, laying a strong foundation for future studies.
This addendum serves to supplement the standard mathematics curriculum for Class 4 students, providing additional resources, explanations, and activities designed to reinforce key concepts. The aim is to enhance understanding and application of mathematical principles in a fun and engaging manner.
Keywords: Multi-Digit Numbers; Equivalent Fractions